Determination of bioactive compounds in freeze-dried postbiotics derived from Lactobacillus strains and antimicrobial effect of the postbiotics against foodborne pathogens - Akgol, Muzeyyen; Karatepe, Pinar; Al, Serhat; Calicioglu, Mehmet; Hayaloglu, Ali Adnan; Tekin, Ali; Incili, Gokhan Kursad (Elsevier, 2026)
Postbiotics have emerged as a promising bioactive ingredient due to their potential health benefits and applications in the food industry. This study aimed to characterize freeze-dried postbiotics from three Lactobacillus strains (Lactiplantibacillus plantarum ATCC 14917, Lacticaseibacillus casei ATCC 393, and Lactobacillus helveticus ATCC 15009) by evaluating their chemical composition, antioxidant capacity, and in vitro antibacterial activity against major foodborne pathogens. The lyophilized postbiotics contained a diverse range of bioactive compounds, including organic acids, amino acids, fatty acids, polyphenols, and volatile compounds, with significant strain-dependent differences in chemical composition (P < 0.05). All postbiotics exhibited strong antioxidant capacity (ABTS, DPPH, FRAP and CUPRAC), with significant differences observed among the strains (P < 0.05). In addition, the postbiotics exhibited strong antibacterial activity against all tested pathogens, as indicated by low MIC values, clear inhibition zones, and a significant reduction in bacterial counts in the time-kill assays. In summary, the freeze-dried postbiotics derived from different Lactobacillus strains showed strong antioxidant and antibacterial activities. These findings suggest that these postbiotics may represent promising bioactive compounds with potential applications in food preservation, food safety improvement, and the development of functional foods and health-promoting products.
Keywords: Postbiotic; Lactobacillus Spp .; Chemical Characterization; Antibacterial Activity; Food Borne Pathogens